Enhancing Students’ Basic Grammar Mastery Through Translation Tests: A Classroom Action Research Study - Sujatmiko, Sujatmiko (Universitas PGRI Yogyakarta, 2026)
Understanding grammar is fundamental for effective communication and language proficiency. However, many English as a Foreign Language (EFL) students continue to face difficulties in mastering basic grammar rules. This study aims to improve third-semester students’ grammar mastery through the implementation of translation tests within a Classroom Action Research (CAR) framework. The participants consisted of 26 English Education students from Universitas PGRI Yogyakarta. The research was conducted in two cycles involving planning, acting, observing, and reflecting stages. Data were collected through pre-tests, post-tests, questionnaires, and interviews. The findings revealed a significant improvement in students’ grammatical competence after the implementation of translation-based activities. The use of translation techniques, particularly the established equivalent, increased substantially—from 45.34% in the pre-test to 89.89% in post-test II. Moreover, students who passed the minimum passing grade rose from 11.54% in the pre-test to 100% in post-test II. These results indicate that translation tests not only enhance students’ understanding of grammar but also foster better analytical and linguistic awareness. The study concludes that integrating translation tasks into grammar instruction is an effective pedagogical approach to developing students’ grammatical accuracy and confidence in English learning.Keywords: Classroom Action Research, EFL students, Grammar mastery, Translation tests, Translation techniques